Ross's Russian Soviet Republic - Durand, E. Dana; Ross, Edward Alsworth (Quarterly Journal of Economics, 1924)
Journal Article Ross's Russian Soviet Republic1 E. Dana Durand E. Dana Durand Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 38, Issue 2, February 1924, Pages 330–338, https://doi.org/10.2307/1884015 Published: 01 February 1924